2021
DOI: 10.1002/jlb.3ma1220-815rrr
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ-mediated repression of system xc− drives vulnerability to induced ferroptosis in hepatocellular carcinoma cells

Abstract: IFNγ released from CD8+ T cells or natural killer cells plays a crucial role in antitumor host immunity. Several studies have found that IFNγ is involved in regulating tumor cell proliferation and apoptosis. However, few studies have examined its role in cell ferroptosis. Here, we found that IFNγ treatment enhanced glutathione depletion, promoted cell cycle arrested in G0/G1 phase, increased lipid peroxidation, and sensitized cells to ferroptosis activators. Additionally, IFNγ down‐regulated the mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 45 publications
0
67
0
Order By: Relevance
“…A study investigated the effect of IFNγ on hepatocellular carcinoma (HCC) found that IFNγ enhanced the consumption of GSH, increased lipid peroxidation, and increased the sensitivity of HCC to ferroptosis. At the same time, IFNγ induces ferroptosis in HCC by activating JAK/STAT signal transduction and inhibiting system ( 76 ). But in TME, NK cells dysfunction occurs.…”
Section: Immune Cells and Ferroptosismentioning
confidence: 99%
“…A study investigated the effect of IFNγ on hepatocellular carcinoma (HCC) found that IFNγ enhanced the consumption of GSH, increased lipid peroxidation, and increased the sensitivity of HCC to ferroptosis. At the same time, IFNγ induces ferroptosis in HCC by activating JAK/STAT signal transduction and inhibiting system ( 76 ). But in TME, NK cells dysfunction occurs.…”
Section: Immune Cells and Ferroptosismentioning
confidence: 99%
“…Recently, IFNγ was used to sensitize HCC cells to ferroptosis by suppressing system x c - via activation of the JAK/STAT signaling pathway, thus providing new insights into the feasibility of using IFNγ to induce ferroptosis in treating HCC [ 100 ]. In addition, the progression of HCC was recently linked to the circ0097009/miR-1261/SLC7A11 axis [ 101 ].…”
Section: Introductionmentioning
confidence: 99%
“…e PPAR signaling pathway, antigen processing and presentation, and ferroptosis are associated with cancer growth and metastasis [22][23][24][25][26][27]. For example, the overexpression of the lncRNA TINCR inhibits colorectal cancer (CRC) cell proliferation and promotes apoptosis.…”
Section: Discussionmentioning
confidence: 99%